AB0516 An open-label randomized controlled study to evaluate the efficacy of etanercept (ETN) versus rituximab (RTX), in patients with active rheumatoid arthritis previously treated with RTX and TNF blockers. (23rd January 2014) - Combe, B.; Dougados, M.; Logeart, I.; Lukas, C.; Mariette, X.; Puechal, X.; Saraux, A.; Schaeverbeke, T.
Abstract : Background: In patients with active RA and inadequate response to several lines of biologics including TNF blockers and RTX, there is no recommendation for therapeutic strategy. It has been suggested that the changes in the immune reaction after B-cell depletion may facilitate the efficacy of previous therapies such as TNF blockers. Objectives: To evaluate efficacy and safety of retreatment with ETN + MTX versus an additional course of RTX + MTX, in RA patients who experienced inadequate response to ETN then RTX. Methods: This open-label, multicentre, randomized study was designed to include patients with active RA (DAS28>4.4) and previous inadequate response to one or two courses of RTX in the last 6-9 months and to at least one TNF blockers including ETN. Patients received ETN (50 mg/week) + MTX or RTX (1 g x 2) + MTX during 6 months. The sample size calculation was based on 20-30% EULAR responders in the RTX group versus 45-55% in the ETN group which required inclusion of 110 patients. Results: The study was stopped after one year due to recruitment failure. Twenty patients (10 in each group) were randomised and followed during 6 months. The efficacy results are reported on the table. One severe adverse event related to treatment was reported in the RTX group (severe infusion reaction). Conclusions: This controlled study confirms preliminary reports of cases and suggests that a retreatment with ETN in RA patients who previously failed TNF blockers then RTX, could be efficient. Disclosure of Interest: B. COMBE Grant/Research support from: PFIZER, M. DOUGADOS Grant/Research support from: PFIZER, I. LOGEART Employee of: PFIZER, C. LUKAS Grant/Research support from: PFIZER, X. MARIETTE Grant/Research support from: PFIZER, X. PUECHAL Grant/Research support from: PFIZER, A. SARAUX Grant/Research support from: PFIZER, T. SCHAEVERBEKE Grant/Research support from: PFIZER